Performance analysis of associated gas transport in a multiphase pipeline - Fallah, Tawba; mabrouk, Aicha; Belghaieb, Jalel; Hajji, Nejib (IJRDO-Journal of Applied Science, 2019)
The aim of this paper is to evaluate the fraction of gas that can be safely transported in a multiphase pipeline instead of flaring it at the production site. The Olga software was used to estimate the pressure increase in the pipeline due to the injection of the gas. Furthermore, potential flow assurance problems were checked using the same software. It was found that all the produced gas can be safely injected in the pipeline as the resulting pressure increase did not reach its maximum allowable operating pressure (MAOP). Hydrate formation and slug problems were predicted by Olga. It was shown that they can be readily handled using a slug catcher for the first and Mono-ethylene Glycol (MEG) injection for the second.